Pembelajaran Project Based Learning Berbantuan Geoegebra untuk Meningkatkan Kemampuan Berpikir Komputasi dan Resiliensi Matematis Siswa - Saragih, Martin Valerian Amadeus; Nurjanah, Nurjanah; Yulianti, Kartika (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2025)
This study attempts to enhance high school learners' computational thinking and mathematical resilience skills. This study employs quantitative approaches with a quasi-experimental research design, and the type of research is Non-Equivalent Group Design. The tools used in this study were computational thinking skills tests and mathematical resilience questionnaires. From the results of the survey conducted, it is known that: 1) the Project Learning model accompanied by GeoGebra significantly improves computational thinking skills, and Project-Based Learning model has moderate improvement; 2) computational thinking skills of high school students who were taught through Project-Based Learning model aided by GeoGebra improved significantly compared to those taught with the Project-Based Learning model; 3) Project-Based Learning model aided by GeoGebra has a positive effect on the mathematical resilience of high school students, but only to a moderate extent.